BASIC TEACHING SKILLS IN ELEMENTARY SCHOOLS - Steven C. Belzer (SENSEI RESEARCH CENTER, 2021)
The skill of opening and closing this lesson is neither easy nor difficult, but sometimes the teacher forgets the importance of this skill. The purpose of this research is to find out about the nature of basic teaching skills, especially the opening and closing parts of learning. The method used in this research is literature study. The results of this study are that there are 8 KDM which are considered very instrumental in the success of teaching and learning activities, namely questioning skills, reinforcement skills, variations skills, explaining skills, skills of opening and closing lessons, skills of guiding small group discussions, skills of managing classes, skills teach small groups and individually.